Acid-extrusion from tissue: the interplay between membrane transporters and pH buffers. - Hulikova, A; Harris, A; Vaughan-Jones, R; Swietach, P (2012)
The acid-base balance of cells is related to the concentration of free H⁺ ions. These are highly reactive, and their intracellular concentration must be regulated to avoid detrimental effects to the cell. H⁺ ion dynamics are influenced by binding to chelator substances ('buffering'), and by the production, diffusion and membrane-transport of free H⁺ ions or of the H⁺-bound chelators. Intracellular pH (pHi) regulation aims to balance this system of diffusion-reaction-transport processes at a favourable steady-state pHi. The ability of cells to regulate pHi may set a limit to tissue growth and can be subject to selection pressures. Cancer cells have been postulated to respond favourably to such selection pressures by evolving a better means of pHi regulation. A particularly important feature of tumour pHi regulation is acid-extrusion, which involves H⁺-extrusion and HCO₃⁻-uptake by membrane-bound transporter-proteins. Extracellular CO₂/HCO₃⁻ buffer facilitates these membrane-transport processes. As a mobile pH-buffer, CO₂/HCO₃⁻ protects the extracellular space from excessive acidification that could otherwise inhibit further acid-extrusion. CO₂/HCO₃⁻ also provides substrate for HCO₃⁻-transporters. However, the inherently slow reaction kinetics of CO₂/HCO₃⁻ can be rate-limiting for acid-extrusion. To circumvent this, cells can express extracellular-facing carbonic anhydrase enzymes to accelerate the attainment of equilibrium between CO₂, HCO₃⁻ and H⁺. The acid-extrusion apparatus has been proposed as a target for anti-cancer therapy. The major targets include H⁺ pumps, Na⁺/H⁺ exchangers and carbonic anhydrases. The effectiveness of such therapy will depend on the correct identification of rate-limiting steps in pHi regulation in a specific type of cancer.